Sabbatical leave report: sabbatical Fall 2012 / submitted by: Susan J. Westrick, Professor, Department of Nursing. - Westrick, Susan J. (2012)
This sabbatical project involved re-writing as the sole author a previously co-authored textbook, Essentials of Nursing Law and Ethics (2009), devoted to traditional and contemporary legal and ethical concerns for nursing students and practicing nurses.
Keywords: dept.nur; faculty_collection; sabbatical_report